Effects of four different enteral feeding methods on tumor Necrosis Factor-α (TNF-α) and high sensitive C-Reactive Protein (hs-CRP) in critically Ill Patients: double blinded, randomized controlled trial - Mousavi Jazayeri, Seyed Mohammad Hosein; Ostadrahimi, Alireza; Safaiyan, Abdolrasoul; Hashemzadeh, Shahryar; Salehpour, Firouz (Progress in Nutrition, 2016)
Background: Despite advances on nutrition in Intensive Care Unit (ICU), effects of different nutritional treatments and methods on inflammatory markers are still controversial in critically ill patients. This study was designed to examine the effects of four different methods of enteral feeding on serum levels of tumor necrosis factor-α (TNF-α) and high sensitive C-reactive protein (hs-CRP) in surgical ICU patients. Methods: In a double blinded, randomized controlled trial, 25critically ill patients were recruited. They randomly divided to four groups regarding enteral feeding: early closed (EC), delayed closed (DC), early opened (EO) and delayed opened (DO). Blood samples were obtained to measure TNF-α and hs-CRP on day 1st, 3rd, 5th and 7th by using ELISA method. Results: Monitoring of TNF-α and hs-CRP revealed a significant elevation of these inflammatory factors at 3rd day of ICU admission (P< 0.001) and a significant decrease on 5th and 7thdays (P